Glyphosate in oat desiccation for haylage harvest at different wilting times - Horst, Egon Henrique (2022)
The objective was to evaluate the ruminal disappearance rate of dry matter and NDF of black oat haylage subjected to mechanical and chemical dehydration and six wilting periods in the field, as follows: 0, 3, 6, 9, 12 and 15 days. Forage haylages were ensiled and stored in PVC mini-silos for 60 days until opening for in situ evaluations. The pre-set ruminal incubation times were: 0, 6, 12, 24, 36 and 48 hours. Regardless of the dehydration time, forage subjected to mechanical dehydration showed ruminal disappearance rates of dry matter and NDF, thus DISDM-48h and DISNDF-48h were superior for this method compared to the chemical method. There was a reduction in DISDM-48h and DISNDF-48h with advancing time of wilting in the field for haylage dehydrated by the chemical method. In general, the chemical dehydration method seems to be more related to better haylage making practices than nutritional factors, where the haylage obtained by mechanical dehydration is superior.